COMBINATION OF AZILSARTAN MEDOXOMIL AND CHLORTHALIDONE: IS IT POSSIBLE TO FIGHT SYSTEMIC HYPERTENSION AND OBESITY TOGETHER? - Yu. A. Vasyuk; E. Yu. Shupenina; E. A. Nesterova; E. I. Golubkova; V. V. Nesvetov (Российский кардиологический журнал)
Arterial hypertension (AH) and obesity are the main risk factors of chronic noncommunicable diseases. Adipous tissue is not only a depot for energetic compounds, but is an active endocrine organ synthetizing biologically active substances that facilitate development of AH. Patients with AH and obesity are in the high cardiovascular risk group and demand effective combination antihypertension therapy. One of such drugs is the fixed combination of azilsartan medoxomil and chlorthalidone, which safety and efficacy are confirmed by various trials. Our clinical case demonstrates positive action of Edarbi Сlo on office and 24-hour blood pressure (BP), main parameters of aorta stiffness and structural and functional condition of myocardium at rest, as in exertion in patient with AH and obesity.